Determinants of the Growing Importance of the Kaliningrad Oblast’ in International Logistics Chains - Jakub DONSKI-LESIUK (Communications of International Proceedings, 2021)
The article presents the factors that determine the noticeable increase in the importance of the Kaliningrad Oblast in international supply chains. It indicates the reasons for increasing the share of this specific area of the Russian Federation in the flow of goods transported by rail, and shows trends with the use of statistical data analysis. The indicated determinants of pattern have been included taking into account the impact of current political events and technical issues involving alternative logistics corridors. This made it possible to present the figures against the background of the ongoing geopolitical changes.  While the increase in transport to / from Kaliningrad and the volume of cargo in those ports may seem to be an issue resulting from the actions of the managers of the Russian transport infrastructure, it has an impact on the international position of neighboring countries, including Poland, Lithuania or Latvia. The practical implications of the conclusions may be useful at the strategic planning stage of entities interested in ensuring the diversification of Trans-Eurasian Logistics Chains.
Keywords: Kaliningrad Oblast’; cross-border freight; international exchange of goods; Trans-Eurasian international flows